2005
DOI: 10.1103/physrevb.72.045205
|View full text |Cite
|
Sign up to set email alerts
|

Reactions and diffusion of atomic and molecular oxygen in theSiO2network

Abstract: To address the reactions and diffusion of atomic and molecular oxygen in SiO 2 , the modification of the SiO 2 network on exposure to an atomic or molecular oxygen atmosphere is investigated by measuring the x-raydiffraction profile of the residual order peak emanating from the oxide. Analyses of the peak intensity and its fringe pattern provide experimental evidence for the recent theoretical predictions, indicating that atomic oxygen is incorporated into the SiO 2 network near the surface and diffuses toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
(27 reference statements)
0
20
0
Order By: Relevance
“…Oxygen atoms in a plasma have been reported to react with the SiO 2 network near the surface and diffuse toward the interface by changing bond connections. 11,21 In the O 2 /He plasma, high-energy He ions would assist oxygen atoms in changing the bonding and reconstructing the SiO 2 network by breaking bonds with impurities. Figure 4 shows the correlation between the Si-H and E 0 center concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen atoms in a plasma have been reported to react with the SiO 2 network near the surface and diffuse toward the interface by changing bond connections. 11,21 In the O 2 /He plasma, high-energy He ions would assist oxygen atoms in changing the bonding and reconstructing the SiO 2 network by breaking bonds with impurities. Figure 4 shows the correlation between the Si-H and E 0 center concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10] Plasma treatments generate a high density of excited oxygen atoms, which react with the SiO 2 network at temperatures typically too low for oxygen molecules reaction. 11 In previous reports, it was concluded that the SiO 2 network was reconstructed by SPA plasma treatments, which led to a reduced leakage current. To investigate which active species in the SPA plasma are most effective in improving the oxide film characteristics, we have treated ALD oxide films with various plasmas and investigated the dependence of the physical and electrical characteristics on the type of inert gas, O 2 partial pressure (P O2 ), and total plasma pressure.…”
mentioning
confidence: 98%
“…(8)) [74]. Furthermore, a recent X-ray diffraction study has shown that the migration of interstitial O 0 is accompanied by a significant rearrangement of the Si-O network, which is not caused by the diffusion of interstitial O 2 [91]. Thus, interstitial O 0 probably forms POL in the Si-O network.…”
Section: Configuration In A-sio 2 Networkmentioning
confidence: 94%
“…There have been many studies on the diffusion/transport of atomic and molecular oxygen, as well as other species like CO, through silica and related materials. Tatsumura et al reported that atomic and molecular oxygen diffuse in silica at temperatures as low as 400 and 850 • C, respectively [37]. Roy et aldiscussed the oxidation of silicon carbide in oxygen at around 1000 • C [38].…”
Section: Mechanism Of Cnt Scaffold Removal From Under Silicon Nitridementioning
confidence: 99%